High Resolution Attenuation Images From Active Seismic Data: The Case Study of Solfatara Volcano (Southern Italy) - De Landro, Grazia; Serlenga, Vincenzo; Amoroso, Ortensia; Russo, Guido; Festa, Gaetano; Zollo, Aldo (Frontiers in Earth Science, 2019)
The quality factor Q is highly sensitive to the medium properties related to the fluid presence, like porosity, permeability and level of rock saturation. Therefore, it is very useful to image the subsoil of volcanoes in terms of anelastic images, in addition to more common elastic tomographic models. In this geological structure, indeed, fluids play a key role in controlling and governing the evolution of magmatic processes, so their accurate identification and tracking is crucial. Here, we describe a methodology that allows to obtain accurate 1-D and 3-D attenuation models from seismic active data. It has been applied to a small-scale volcanic volume of the shallow Solfatara crater, in southern Italy. Our purposes were achieved in three steps: 1/ we measured the attenuation parameter t* from active survey data, first by cross-correlating the signal with the sweep function and then by using the spectral decay method; 2/ we determined a reference 1-D attenuation model for the area through a grid model search procedure; 3/ we reconstructed the 3-D attenuation model through an iterative inversion of t* data. In order to validate the t* catalogue, we analyzed the map of t* residuals with respect to the reference 1-D model... The shallowest subsoil of Solfatara is characterized as a volume with a P-wave quality factor, QP, which increases with depth and has a high lateral anelastic heterogeneity. QP can be therefore considered as a proxy for the detection of strong variations both in fluid saturations and in the type of fluids permeating the shallowest volcanic sediments of the investigated volume.